High-Frequency Ultrasonography—Possibilities and Perspectives of the Use of 20 MHz in Teledermatology - Polańska, Adriana; Jenerowicz, Dorota; Paszyńska, Elżbieta; Żaba, Ryszard; Adamski, Zygmunt; Dańczak-Pazdrowska, Aleksandra (Frontiers in Medicine, 2021)
High-frequency ultrasonography (HF-USG) is a non-invasive and in vivo method of visualization of the skin and upper part of subcutaneous tissue based on ultrasounds above 20 MHz. Although initially HF-USG was introduced to measure skin thickness, it currently gained widespread acceptance in dermato-oncology, primarily when used to determine skin tumor margins. Moreover, its application in different dermatology fields is known, particularly as a rapidly evolving method in the objective evaluation of the severity of various chronic skin diseases. Among different specialties, teledermatology belongs to leading and continually developing areas of successful telemedicine applications. Various skin conditions are visible to the human eye, which makes them particularly suitable for telemedicine. However, HF-USG enables specialists to look into deeper skin layers, thus extending diagnostic options. On the other hand, teledermatology creates the possibility of sending images for consultation and facilitates the therapeutic decision as HF-USG can be used in an asynchronous store and forward manner. It seems that HF-USG and teledermatology may be regarded as a truly matched pair. The aim of this work is to present current applications of 20-MHz ultrasonography in dermatology, including skin neoplasms and chronic skin diseases. Moreover, the authors aimed to analyze the possibilities of HF-USG use as a valuable tool in teledermatology, especially in diagnosing and monitoring patients suffering from long-lasting skin conditions.